Combating illegal immigration to the EU - Vaitkeviciute, Agne (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2020)
Transport companies or carriers contribute to immigration processes into the European Union in that they carry third-country nationals across EU external borders to the territory of the EU Member States. As part of the fight against illegal migration, the EU assigned specific responsibilities to carriers within the context of external borders control. Carriers are obliged to perform checks to verify whether the transported third-country nationals have the necessary travel documents. Moreover, they have to transmit certain (air) passenger data to competent national authorities. In cases of failure to comply with these obligations, transport companies face dissuasive, effective and proportionate sanctions. Besides, carriers must assume responsibility for all third-country nationals on board if they are refused entry. The EU Member States can oblige carriers to return these third-country nationals to respective third countries. The author briefly analyses the EU legislative framework regarding international transport companies. To delineate the scope of carriers` obligations towards competent border authorities of the EU Member States and to identify which particular role carriers play in combating illegal immigration to the EU, the applicable legal framework (namely the Carrier Sanctions Directive, the Passenger Data Directive and, to a certain extent, the Removal Directive) are be discussed. Additionally, sanctions that transport companies face for non-compliance with these obligations are discussed to assess whether the directives in their current versions can be regarded as creating a proper legal basis for sanctioning carriers. Finally, the author analyses which particular aspects still need to be clarified so that the role assigned to international transport companies in the fight against illegal immigration to the EU is clear and unambiguous and that illegal immigration to the EU can be effectively constrained.